CALCULATION OF LOSSES OF ACTIVE POWER AND ENERGY IN TRANSMISSION LINES AND TRANSFORMERS, AS A PART OF THE ELECTRICAL DISTRIBUTION POWER NETWORK (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The paper inhere discusses the impact of renewable distributed generation sources upon the power and energy losses in electrical distribution power networks where these sources are attached. In addition a set of mathematical expressions to calculate these active power and energy losses are presented with the respective examples and implementation.